Ineffectiveness of the Smart City Program in the Demographic Field (Study on the Use of E-SIAP in Disepndukcapil Blitar Regency) - Rosy Nursita Anggraini; Fadilah Amin; Imam Hanafi (Wacana Journal of Social and Humanity Studies, 2020)
Smart city is a program that has been implemented by various countries, including Indonesia. The application in different countries is also different. In other words, this program is adjusted to the capabilities of each country and citizens. This program has many derivative programs in various fields, including the demographic field which in serving the community related to ownership of population documents utilizing E-SIAP. The purpose of writing this scientific paper is to find out the cause of ineffectiveness in the use of E-SIAP. In writing this scientific paper using qualitative research methods with the type of descriptive research to illustrate the ineffectiveness of E-SIAP in Blitar District. By using an interactive analysis model that was initiated by Miles and Huberman to analyze the ineffectiveness of E-SIAP such as the causes of the program that was not well understood, not on target, not on time, and not achieving its goals. In other words, the government must continue to increase the effectiveness of the use of E-SIAP to realize the stated goals of the agency.